LIGHT CONTROL SYSTEM WITH INTERNET OF THINGS (IOT) AND BLUETOOTH TECHNOLOGY USING NODE MCU - Aldi Burhannudin; Isra' Nuur Darmawan; Priyono Yulianto; Eko Sudaryanto (Journal of Electronic and Electrical Power Applications, 2022)
Controlling lights at home can actually be done manually, but with the development of technology in the modern era, there are many ways to control lights, for example remotely using IoT technology, using bluetooth and can also use remote controls. This study aims to create a modern light control system with internet of things and Bluetooth media. The NodeMCU microcontroller was chosen as the brain of the control system, because there is already a module that can be connected to the internet. The input of the control system uses the HC-05 bluetooth module, while for the output it uses the relay module. After testing both software and hardware, the result is that the response speed after sending data from the two media has different vulnerabilities, IoT media has a response that depends on the internet network used with an average of 1.38 seconds turning on the lights and turning off the lights 1, 61 seconds, while with bluetooth media has a very good response, namely to turn on the lights 0.18 seconds and turn off the lights 0.24 seconds. This control system cannot use both media simultaneously and when it is first turned on the system must be connected to the internet first so that bluetooth media can be run or used.